Research on enhancing the mechanical strength of polyvinyl alcohol/sodium alginate gel beads applied in biological wastewater treatment - Nguyễn Văn, Tuyến; Tran Hung Thuan; Do Quang Trung (Journal of Military Science and Technology, 2022)
This study investigated a new type of polyvinyl alcohol-sodium alginate (PVA/SA) gel beads for immobilization of activated sludge biomass. Gel beads are made from PVA, SA, and graphene oxide (GO) with different concentrations of GO (0.02, 0.2; 2; 20 and 200 mg/L). The results showed that the basic properties, including the roundness and expansion rate of the gel beads, did not differ significantly between the GO concentrations. At the same time, the higher the concentration of go, the more it improves the mechanical strength of the gel beads. The highest strength was when GO levels reached 200 mg/L. At the same concentration, the gel beads achieved the highest methylene blue absorption capacity (91.2%) and the fastest oxygen consumption rate (0.31 mg/L/min) compared to PVA/SA gel beads without GO. This result initially demonstrated that the addition of GO is an effective way to enhance the mechanical strength of PVA/SA gel beads.